Identities in exile: re-membering identities, re-membering the nation in Laksmi Pamuntjak's amba - Ahmad, Siti Nuraishah (Department of English of the Ateneo de Manila University, Philippines., 2019)
Laksmi Pamuntjak’s first novel, Amba (2012) is one of several contemporary Indonesian novels by the post-1965 generation that breaks the silence on the violent suppression of the Indonesian left in the mid-1960s. Like other recent creative responses and initiatives by Indonesian artists and civil society, Amba represents the “postmemory” of the 1965-66 events. This paper examines the modes of internal exile triggered by 1965 as portrayed in three characters in Amba and how exile disrupts and delays identity formation across different generations of Indonesians—hence, exiled identities. The history of Moluccan exile post-1950 is also crucial to the novel’s representation of people whose identities were displaced, ruptured, or in limbo as a result of political violence. The depiction of internal exile in Amba is examined based on work done by scholars on Indonesian exile narratives (Hill, Hearman) and concepts of transgenerational trauma (Schwab) and postmemory (Hirsch). This paper then discusses the various acts of “re-membering” to recover a coherent sense of self and of the nation depicted in Amba, such as through literal and figurative journeys, re-establishing kinship ties, narrating personal memories of the traumatic past, and the role of art in revealing suppressed memories of the 1965 event.